2016
DOI: 10.5539/ijel.v6n4p144
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Professional Development: EFL Teachers’ Experiences in the Republic of Benin

Abstract: Using a survey, this study examines EFL teachers' views on professional development, the models of teacher development they are familiar with, and their experiences in the area. The study also inquires into the teachers' knowledge and opinions about inquiry-based teaching. The results indicate that though the EFL teachers often have the opportunity to participate in teacher development activities, these activities do not enable them to develop the skill of reflection and action on practice as they are patterne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In the Republic of Benin, Agbayahoun (2016) conducted a survey with 157 secondary EFL teachers in order to explore their views on PD, the models of teacher development they were familiar with, and their experiences in the area. The results reported that the PD activities teachers frequently engaged in were one-shot courses that followed top-down models, so these activities could not assist teachers to enhance their skills in reflection and action on practice.…”
Section: Teachers' Participation In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Republic of Benin, Agbayahoun (2016) conducted a survey with 157 secondary EFL teachers in order to explore their views on PD, the models of teacher development they were familiar with, and their experiences in the area. The results reported that the PD activities teachers frequently engaged in were one-shot courses that followed top-down models, so these activities could not assist teachers to enhance their skills in reflection and action on practice.…”
Section: Teachers' Participation In Pdmentioning
confidence: 99%
“…This view is supported by other international scholars. As argued by Agbayahoun (2016) and Wyatt and Ončevska Ager (2017), both top-down and bottom-up approaches should be combined in order to enhance the effectiveness of teachers' PD. This argument is reaffirmed through Anderson's (2018) model of an interactive PD approach, which integrates both input from institutional needs analyses and from individuals who have defined their PD needs.…”
Section: Top-down National Requirementsmentioning
confidence: 99%
“…Other researchers also noted that viewing videos of peer microteaching can also focus pre-service teachers’ attention on particular features of their teaching like classroom management (Setyaningrahayu et al, 2019) that they might otherwise ignore (Galvis & Nemirovsky, 2003). They also observed that reflection upon peer feedback can make novice teachers aware of their unconscious behaviors while teaching (Serdar Tülüce & Çeçen, 2018) that they might not have considered (Agbayahoun, 2017) and the effect that those actions can have on their lesson (Eröz-Tuğa, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In order to gather information on the teachers" experiences of EFL teachers with professional development, a questionnaire item asked about the activities they had engaged in during the year prior to the study and offered the following collection of response options to choose from: state-run annual training workshops, TEFL 6 Agbayahoun (2016), additionally, based on theory, "analysis distinguishes between top-down and bottom-up teacher development models" (Johnson, 2006;Kumaravadivelu, 2003;Richards, 2008;Richards & Farrell, 2005 2005), some professional development practices are explained as follows: workshop, self-monitoring or self-observation, peer observation, peer coaching, study groups, team teaching, dialog journals or keeping a teaching journal, professional development portfolios, mentoring, analyzing critical incident, case analysis, participatory practitioner research.…”
Section: Research Context: Tpd Learning Activitiesmentioning
confidence: 99%
“…Some of them, focus on the teacher professional development has been reported to be beneficial, both in ESL (English as a Second Language) and EFL (English as a Foreign Language) context (see Bell & Gilbert, 1994;Bell & Mladenovic, 2008;Christodoulou, 2010;Dasrizal, 2009;Drew & Klopper, 2014;Karaaslan, 2003;Lan & Wang, 2013;Maisa, 2009;Mardiana, 2013;Pajarwaty, 2009;Sadler, 2012;Subramanian & Genni, 2013;Thongthai, 2011;Warahmah, 2009;Yani, 2012;Zepke & Stevens, 1987). Another study concerning EFL teachers" views on professional development, the models of teacher development they are familiar with, and their experiences in the area (Agbayahoun, 2016). The results indicate that though the EFL teachers often have the opportunity to participate in teacher development activities, these activities do not enable them to develop the skill of reflection and action on practice as they are patterned on top-down models of teacher development and happen in a one-shot workshopstyle.…”
Section: Introductionmentioning
confidence: 99%